Enhancing Students Grammar by Writing Journals (A Case Study: Analyzing a Student’s Journal in One Semester) - Nita Henita Koesoemah (Jurnal Bahasa Inggris Terapan, 2017)
The title of the research report is Enhancing Students Grammar by Writing Journals (a case study: analyzing a student’s journal in one semester). The aim of the research is to analyze how writing journals can enhance students grammar of English which is influenced by Indonesian. As there is a big difference of present-past form of the verbs in both Indonesian and English, this research focused on those forms. The errors found in the students’ journals were analyzed. To get the answer of the aims, descriptive method is used. The data source is one student’s journal which is written in one semester (semester 2) by one of the students of 2012 English department. The result obtained is that there is an improvement in students’ grammar (in this research the use of present-past form the verbs) through writing journals. Key words: enhancing, journals , grammar